TRAFFIC IMPACT ANALYSIS REVIEW OF TRAVEL ATTRACTION IN THE AREA OF PANKEP REGENCY Hospital - Maryam H; Lambang Basri Said (Moeslim Indonesian University (UMI), 2020)
The activity zone is located as a trip towing zone. One of these activity zones is the Hospital. The Pangkep District General Hospital which is located in the city center of Pangkep Regency has a fairly high activity intensity. The interactions that occur as a result of the need for health, both patients and families or visitors as well as medical officers or hospital managers and others will result in the movement of traffic flows around the hospital complex which will cause problems including an increase in traffic volume on the toll segment. the road that is around the Pangkep Regional General Hospital. This study aims to find out how many pulls occur at the Pangkep Regional General Hospital, to find the contribution of the distribution of traffic that occurs on the roads around the Pangkep Regional General Hospital and the road capacity that is burdened by visitors to the Pangkep Regional General Hospital. In this study, a survey method with a questionnaire was conducted to determine the socio-economic characteristics. The sampling technique was carried out in a proportional random manner for each visitor who used a certain mode to reach the Pangkep Regional General Hospital which represented all zones. Based on the analysis results, predictions for the next 10 years will increase the intensity of activities at the Pangkep Regional General Hospital, in 2019 the Pangkep Regional General Hospital with a building area of ​​± 10,885 m2 is able to attract 172 cars per day and 581 motorbikes per day, as well as attracting 1207 visitors per day, in the next 10 years the Pangkep Regional General Hospital will attract as many as 206 cars per day and 697 motorcycles per day, and attract 1447 visitors per day. The performance of the road segment has almost reached the upper safe limit, as indicated by the DS which has reached 0.31 in 2019 and the DS will increase to 0.45 in 2029.